Fontan-associated liver disease in children following surgical correction of congenital heart defects - Zientarska, Agata; Ludwikowska, Kamila; Szenborn, Leszek (Clinical and Experimental Hepatology, 2026)
The Fontan procedure is a palliative surgical strategy used in the management of severe congenital heart defects, resulting in the creation of a single-ventricle circulation. In this physiological configuration, venous blood from the systemic circulation flows directly into the pulmonary arteries, bypassing the heart muscle. The operation is typically performed in early childhood and significantly improves long-term prognosis, enabling survival into the third decade of life and beyond. Over time, however, children and young adults develop complications related to the altered circulatory system, including chronic liver disease predominantly driven by passive hepatic congestion. This condition leads to progressive hepatic fibrosis, cirrhosis, and, in a substantial proportion of patients, hepatocellular carcinoma. Consequently, lifelong interdisciplinary specialist care, including structured hepatological follow-up, is required from early childhood. Progressive liver disease in children with altered cardiovascular physiology poses distinct diagnostic and therapeutic challenges.